The Predictive Value of the Pentraxin 3 Concentration in Cumulus Cell Culture Media for the Embryo Implantation - Tulay Irez; Yavuz Sahin; Eduard Malik; Onur Guralp (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Many studies on the interrelation of cumulus cells and oocytes, and research on cumulus protein factors continue. This study aims to investigate the relationship of Pentraxin 3 level with embryo implantation in the cumulus culture fluid.